Upgrade the vocabulary comprehension of students in middle school using the Drops application tool - Baroro, Faidatul; Nisa’, Dwi Khoirotun; Maulana, Asep; Irawan, Bambang (Abjadia : International Journal of Education, 2025)
Drops is a language learning tool designed to help users memorize vocabulary in various languages, including Arabic. Developed in Estonia and acquired by Kahoot in 2020, Drops aims to make learning engaging and accessible. In the context of Arabic learning at Islamic Junior High School  Situbondo, students often find the subject challenging and uninteresting. The use of Drops is expected to improve student engagement.This study involved two 8th grade : Class 8E as the experimental group and Class 8A as the control group. A true experimental design with pre-tests and post-tests was used. Data were collected through tests and analyzed using statistical methods, including t-tests.Results showed significant improvements in the experimental group, with scores rising from 50 on the pretest to 90 on the posttest, while the control group’s scores increased from 65 to 80. Statistical tests confirmed significant differences (p 0.05), concluding that Drops media is effective for Arabic learning.